Ethnics differences in perceptions of inequality in health care access in Peru - Intimayta-Escalante, Claudio (2024)
Objectives. To evaluate the differences in the perception of inequality in access to health care according to the ethnic group with which Peruvian adults identify. Material and Methods. Analytical cross-sectional study conducted with a secondary analysis of data from the I National Survey of Perception of Inequalities 2022. The dependent variable was the perception of inequality in the access to health and the independent variables were sociodemographic characteristics. Differences in the perception of inequality in the access to health care according to the ethnic group were evaluated with Poisson-type generalized linear models to estimate the crude and adjusted Prevalence Ratio (aPR) for the other variables. Results. Of the 1,530 respondents, 50.2% were female and the mean age was 40.0 years (95%CI: 39.23 - 40.73). For 71.8%, access to health was very unequal. And the prevalence of a perception of a very unequal access to health was higher in those who identified themselves as part of the natives’ peoples (RPa: 1.19; 95%CI: 1.02 - 1.39; p=0.025) or mestizos (RPa: 1.16; 95%CI: 1.02 - 1.33; p=0.025), when compared with those who identified themselves as white. Conclusion. Seven out of ten Peruvian adults perceived a very unequal access to health care and this perception was higher in those who identified themselves as part of the natives’ peoples or mestizos, when compared to those who identified themselves as white.